Anisotropic tough double network hydrogel from fish collagen and its spontaneous in vivo bonding to bone. (July 2017) - Mredha, Md. Tariful Islam; Kitamura, Nobuto; Nonoyama, Takayuki; Wada, Susumu; Goto, Keiko; Zhang, Xi; Nakajima, Tasuku; Kurokawa, Takayuki; Takagi, Yasuaki; Yasuda, Kazunori; Gong, Jian Ping
Abstract: Soft supporting tissues in the human body, such as cartilages and ligaments, are tough materials and firmly fixed to bones. These soft tissues, once injured, cannot regenerate spontaneously in vivo . Developing tough and biocompatible hydrogels as artificial soft supporting tissues would substantially improve outcomes after soft tissue injury. Collagen is the main rigid component in soft connective tissues which is organized in various hierarchical arrays. We have successfully developed a novel class of collagen fibril-based tough hydrogels based on the double network (DN) concept using swim bladder collagen (SBC) extracted from Bester sturgeon fish. The DN hydrogels, SBC/PDMAAm, are composed of physically/chemically crosslinked anisotropic SBC fibril as the first network and neutral, biocompatible poly(N, N′-dimethylacrylamide) (PDMAAm) as the second network. The anisotropic structure of SBC fibril network, which is well retained in the DN hydrogels, is formed by free injection method, taking advantage of the excellent fibrillogenesis capacity of SBC. The denaturation temperature of collagen is improved in the DN hydrogels. These DN gels possess anisotropic swelling behavior, exhibit excellent mechanical properties comparable to natural cartilage. The 4 weeks implantation of the gels in the osteochondral defect of rabbit knee also shows excellent biomechanical performance in vivo . Furthermore, the hydroxyapatite (HAp) coated DN gels, HAp/SBC/PDMAAm gels, strongly bond to bone after 4 weeks. This new class of collagen-based hybrid DN gels, as soft and elastic ceramics, having good biomechanical performance and strong bonding ability with bone would expand the choice for designing next-generation orthopedic implants such as artificial cartilage, bone defect repair material in the load-bearing region of the body. Graphical abstract: Highlights: Swim bladder collagen (SBC)-based tough double network (DN) hydrogels. Shear and diffusion induced anisotropic structure formation of SBC fibril hydrogels. Excellent biomechanical performances. HAp coated collagen DN gel spontaneously bond to bone in vivo . Potential biomaterials as load-bearing implants.